2020
DOI: 10.1111/cns.13473
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with tuberous sclerosis complex: A pediatric cohort study

Abstract: Aims To evaluate the quality‐of‐life (QOL) impairment and identify the possible risk factors in patients with tuberous sclerosis complex (TSC) in China. Methods The parent proxy‐report PedsQL 4.0 Generic Core Scales were administered to 124 caregivers of children with TSC (aged 2‐18 years). For comparison, the survey was also conducted in a demographically group‐matched sample of healthy controls (HCs) (aged 2‐18 years). Results A total of 124 children with TSC and 206 HCs were recruited. The mean parent proxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 37 publications
0
15
1
6
Order By: Relevance
“…Of note, epilepsy was found to be an independent predictor for poorer HRQoL in Ding Y et al's study, which targeted children with TSC (30), but not in our study which targeted adult and pediatric TSC patients. This may be related to the proxy-reported nature of questionnaires used in evaluating QoL of children.…”
Section: Comparison With Other Studies On Qol Of Tsc Populationcontrasting
confidence: 84%
See 2 more Smart Citations
“…Of note, epilepsy was found to be an independent predictor for poorer HRQoL in Ding Y et al's study, which targeted children with TSC (30), but not in our study which targeted adult and pediatric TSC patients. This may be related to the proxy-reported nature of questionnaires used in evaluating QoL of children.…”
Section: Comparison With Other Studies On Qol Of Tsc Populationcontrasting
confidence: 84%
“…There are two recent studies conducted in Asia assessing the QoL of TSC patients in Malaysia and mainland China respectively (29,30). We compared these two studies with our study and identi ed 3 distinctive differences.…”
Section: Comparison With Other Studies On Qol Of Tsc Populationmentioning
confidence: 97%
See 1 more Smart Citation
“…The panel de ned six levels of investigation: behavioral, psychiatric, intellectual, academic, neuropsychological, and psychosocial level [2,3]. Neurological and psychiatric complications and kidney disease are often the greatest burdens imposed by TSC, but TAND have not been given enough attention [4,5]. A 2010 survey of members of the British Tuberous Sclerosis Association revealed that only 18% of TSC patients had been assessed or treated for neuropsychiatric disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disease associated with a variety of neurological symptoms, such as epilepsy and developmental disorders, including learning problems and autism spectrum disorder 1–5 . These neurological symptoms constitute the main burden of the disease and seriously affect the quality of life of individuals with TSC 6 …”
mentioning
confidence: 99%